2020
DOI: 10.1111/all.14328
|View full text |Cite
|
Sign up to set email alerts
|

Description of two anaphylaxis phenotypes in children: The utility of a clustering analysis approach

Abstract: Early childhood IgE reactivity to pathogenesis-related class 10 proteins predicts allergic rhinitis in adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…The impact of multiple food allergy/sensitization is also reported as a risk factor for severe anaphylaxis. 8 In 696 patients diagnosed with peanut sensitization in the Mirabel study, allergic multi-morbidity (asthma with atopic dermatitis and/or multiple food allergy) was associated with the severity of peanut-induced allergic reactions. 9 We previously found that allergic comorbidities increase the risk of anaphylaxis recurrence in a cohort of 166 children previously hospitalized for anaphylaxis in pediatric intensive care units.…”
mentioning
confidence: 99%
“…The impact of multiple food allergy/sensitization is also reported as a risk factor for severe anaphylaxis. 8 In 696 patients diagnosed with peanut sensitization in the Mirabel study, allergic multi-morbidity (asthma with atopic dermatitis and/or multiple food allergy) was associated with the severity of peanut-induced allergic reactions. 9 We previously found that allergic comorbidities increase the risk of anaphylaxis recurrence in a cohort of 166 children previously hospitalized for anaphylaxis in pediatric intensive care units.…”
mentioning
confidence: 99%
“…23 But, in French study CMA and HEA constituted only 8% and 7%, of the sample, respectively. 23 Blazowski et al in food systemic allergic reactions, identified two clusters -skin/non-severe respiratory phenotype (81%) and severe respiratory/cardiovascular phenotype, but the study populations are not well comparable, as these authors graded severity by means of the 3-stage scale by Muraro. 24 All these mirror an attempts to characterize more precisely paediatric study population managed due to anaphylaxis.…”
Section: Clinical Phenotypementioning
confidence: 81%
“…23 The first one, with severe anaphylaxis (R&M grade III-IV), mainly due to nut allergy, and multiple atopic comorbidities, and the second one, described as mild anaphylaxis with various triggers and few atopic comorbidities. 23 But, in French study CMA and HEA constituted only 8% and 7%, of the sample, respectively. 23 Blazowski et al in food systemic allergic reactions, identified two clusters -skin/non-severe respiratory phenotype (81%) and severe respiratory/cardiovascular phenotype, but the study populations are not well comparable, as these authors graded severity by means of the 3-stage scale by Muraro.…”
Section: Clinical Phenotypementioning
confidence: 99%
“…Several anaphylaxis phenotypes have been described so far, but only depending on the time of onset (monophasic, biphasic anaphylaxis), on the allergen that triggered the reaction or on the severity of the reaction (13,14) . However, food-induced anaphylaxis is extremely heterogenous, resulting in a clinical picture which differs significantly not only between episodes in the same patient, but even in the case of the same trigger.…”
Section: Anaphylaxis Phenotypesmentioning
confidence: 99%
“…The evaluation of the immunoglobulin E (IgE) specific antibodies in relation to allergenic molecules (the proper allergens) in the main allergen source allowed for the differentiation of particular allergens in terms of the risk of developing severe anaphylaxis (11) . In addition, CRD has contributed to the definition of new FIA phenotypes and endotypes, according to the assumptions of precision medicine, focused on an individual patient (11)(12)(13)(14)(15) . Food-induced anaphylaxis is the leading cause of death due to an acute allergic reaction in children (16) .…”
Section: Introductionmentioning
confidence: 99%